Electrolyte and battery

CN115632162BActive Publication Date: 2026-10-23ZHUHAI COSMX BATTERY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211289468.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-20
Publication Date
2026-10-23
Estimated Expiration
2042-10-20

AI Technical Summary

Technical Problem

但VC阻抗较高,在高压下阻抗增长较快,不利于高电压电池的长期循环稳定性;FEC阻抗较低,但在高温高压下不稳定,容易分解,导致电芯产气、体积膨胀,电池寿命降低等问题

Benefits of technology

[0014](1)本发明的电解液阻抗低;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115632162B_ABST
    Figure CN115632162B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of batteries, in particular to an electrolyte and a battery comprising the electrolyte. The electrolyte comprises a first additive, and the first additive is a bridged cycloalkene compound and a derivative thereof. The electrolyte of the application can have low impedance and high stability after the first additive is added, can form a dense and stable interface film at the interface of the positive and negative electrodes, and can inhibit the side reaction between the electrolyte and the negative electrode; the battery obtained from the electrolyte of the application has low initial impedance, low impedance growth rate, high capacity retention rate, better high-temperature cycle performance and more stable long-term cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, and more specifically to an electrolyte and a battery comprising the electrolyte. Background Technology

[0002] During high-temperature cycling or storage, lithium-ion batteries are prone to complex interfacial reactions between the positive and negative electrodes and the electrolyte, affecting various battery performance characteristics. To improve the high-temperature storage performance of lithium-ion batteries, high-temperature additives such as ethylene ethylene carbonate (VEC), 1,3-propane sulpholactone (PS), and 1,3-propene sulpholactone (PST) are often added to the electrolyte. These high-temperature additives can form a protective film on the surface of the high-nickel positive electrode, inhibiting parasitic reactions between the electrolyte and the high-nickel positive electrode, and also inhibiting the dissolution of metal ions from the high-nickel positive electrode, thereby improving the high-temperature performance of the high-nickel cell. However, these high-temperature additives only provide protection for the positive electrode and cannot effectively protect the negative electrode. Furthermore, the interfacial films formed by these high-temperature additives often have high impedance and impedance growth rate, which, while contributing to improved high-temperature storage performance, cannot guarantee the long-term cycle stability of the battery.

[0003] To simultaneously improve the high-temperature performance of batteries and ensure their long-term cycle stability, additives with positive electrode protection functions, such as VEC, PS, and PST, are often used in combination with negative electrode film-forming additives, such as vinylene carbonate (VC) and fluoroethylene carbonate (FEC). However, VC has a high impedance, and its impedance increases rapidly under high voltage, which is detrimental to the long-term cycle stability of high-voltage batteries. FEC has a lower impedance, but it is unstable under high temperature and high pressure, and is prone to decomposition, leading to problems such as cell gas generation, volume expansion, and reduced battery life.

[0004] Therefore, it is very important to invent a battery with low impedance, good high-temperature cycling performance, and more stable long-term cycling performance. Summary of the Invention

[0005] The purpose of this invention is to overcome the aforementioned problems in the prior art and to provide an electrolyte and a battery comprising the electrolyte. The electrolyte of this invention has low impedance and high stability, and can form a dense and stable interfacial film at the positive and negative electrode interfaces, suppressing further side reactions between the electrolyte and the negative electrode. Batteries using the electrolyte of this invention have low initial impedance, low impedance growth rate, and high capacity retention, exhibiting better high-temperature cycling performance and more stable long-term cycling performance.

[0006] The inventors of this invention have discovered that by reducing the impedance of the electrolyte and improving its stability, the initial impedance of the battery can be reduced, the capacity retention rate of the battery can be improved, thereby enhancing the high-temperature cycle performance and long-term cycle stability of the battery.

[0007] Through further in-depth research, the inventors of this invention discovered that, in order to reduce the impedance and improve the stability of the electrolyte, specific substances can be added to the electrolyte to form a dense and stable interfacial film at the positive and negative electrode interfaces, thereby inhibiting further side reactions between the electrolyte and the negative electrode. The inventors of this invention, through extensive and in-depth research, screened out specific compounds capable of forming a dense and stable interfacial film at the positive and negative electrode interfaces.

[0008] To achieve the above objectives, the first aspect of the present invention provides an electrolyte comprising a first additive, wherein the first additive is a bridged cycloene compound and its derivatives.

[0009] In one example, the first additive has the structure shown in formula (Ⅰ).

[0010]

[0011] Wherein, n is 0, 1, or 2; R1, R2, R3, R4, and R5 are each independently selected from H, F, Cl, Br, I, C1-C6 alkyl, C1-C6 haloalkyl, nitrile-substituted C1-C6 alkyl, C2-C6 alkenyl, and C2-C6 alkynyl.

[0012] The second invention provides a battery in which the electrolyte is the electrolyte described in the first aspect of the invention.

[0013] By employing the above technical solution, the present invention has at least the following advantages compared with the prior art:

[0014] (1) The electrolyte of the present invention has low impedance;

[0015] (2) The electrolyte of the present invention can form a dense and stable interfacial film at the positive and negative electrode interfaces;

[0016] (3) The battery of the present invention has low initial impedance, low impedance growth rate, and high capacity retention rate;

[0017] (4) The battery of the present invention has good high-temperature cycle performance;

[0018] (5) The battery of the present invention has high long-term cycle stability;

[0019] (6) The battery of the present invention has good high-temperature storage performance.

[0020] Other features and advantages of the present invention will be described in detail in the following detailed description section. Attached Figure Description

[0021] Figure 1 The figure shows the capacity retention rate-cycle count curve of the battery prepared with the electrolyte of Example 1 of the present invention at 45°C. Detailed Implementation

[0022] The following provides a detailed description of specific embodiments of the present invention. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the scope of the invention.

[0023] The first invention provides an electrolyte comprising a first additive, wherein the first additive is a bridged cycloalkene compound and its derivatives.

[0024] In one example, the first additive has the structure shown in formula (Ⅰ).

[0025]

[0026] Wherein, n is 0, 1, or 2; R1, R2, R3, R4, and R5 are each independently selected from H, F, Cl, Br, I, C1-C6 alkyl, C1-C6 haloalkyl, nitrile-substituted C1-C6 alkyl, C2-C6 alkenyl, and C2-C6 alkynyl.

[0027] The inventors of this invention have discovered that, due to the high reduction potential of the first additive, it can preferentially undergo a reduction reaction on the negative electrode surface during the first charging process of the battery, in order to form a dense and stable SEI film, thereby suppressing the continued occurrence of side reactions between the electrolyte and the negative electrode. At the same time, since the product of the reduction reaction of the first additive is a substance with a similar network structure, the SEI film formed by the first additive has higher stability and lower impedance.

[0028] By adding the first additive with the aforementioned specific structure to the electrolyte, it has been possible to achieve lower impedance and higher stability than existing technologies. To further improve the effect, one or more of the technical features can be further optimized.

[0029] The first additive may be a bridged cyclic alkene compound or its derivatives.

[0030] In the structure shown in formula (I), the dashed lines indicate that chemical bonds may or may not be present. For example, the dashed lines on the six-membered bridge ring indicate that they can be double bonds or single bonds, as shown in formulas (IV) and (V). The dashed lines on the connecting bond between the six-membered bridge ring and the five-membered ring indicate that they can be double bonds or single bonds, as shown in formulas (II) and (III).

[0031] n can be 0, 1, or 2.

[0032] In one instance, n is 0, and the first additive has the structure shown in formula (II) and / or formula (III).

[0033]

[0034] In one instance, n is 1, and the first additive has the structure shown in formula (Ⅳ) and / or (Ⅷ).

[0035]

[0036] In one embodiment, n is 2, and the first additive has the structure shown in formula (V) and / or (IX).

[0037]

[0038] According to one specific embodiment, the first additive has at least the structure shown in formula (Ⅳ).

[0039] The structures shown in formulas (II), (III), (IV), (VIII), (VIII), and (IX) are network structures. Among the structures shown in formulas (II), (III), (IV), (VIII), (VIII), and (IX), the structures shown in formulas (IV) and (VIII) contain a large number of unsaturated bridged ring double bonds, and the substance with a network-like structure formed by formula (IV) has higher stability. Therefore, the electrolyte containing the first additive having the structure shown in formula (IV) has higher stability.

[0040] R1, R2, R3, R4, and R5 may be the same or different, and each is independently selected from H, F, Cl, Br, I, C1-C6 alkyl, C1-C6 haloalkyl, nitrile-substituted C1-C6 alkyl, C2-C6 alkenyl, and C2-C6 alkynyl.

[0041] The C1-C6 alkyl group is selected, for example, from methyl, ethyl, n-propyl, isopropyl, cyclopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, cyclobutyl, n-pentyl, isopentyl, tert-pentyl, neopentyl, cyclopentyl, 2,2-dimethylpropyl, 1-ethylpropyl, 1-methylbutyl, 2-methylbutyl, n-hexyl, isohexyl, 2-hexyl, 3-hexyl, cyclohexyl, 2-methylpentyl, 3-methylpentyl, 1,1,2-trimethylpropyl, and 3,3-dimethylbutyl.

[0042] The C2-C6 alkenyl group is selected, for example, from vinyl, propenyl, 2-propenyl, isobutylenyl, sec-butylenyl, tert-butylenyl, cyclobutylenyl, n-pentenyl, isopentenyl, tert-pentenyl, neopentenyl, cyclopentenyl, 2,2-dimethylpropenyl, 1-ethylpropenyl, 1-methylbutenyl, 2-methylbutenyl, n-hexenyl, isohexenyl, 2-hexenyl, 3-hexenyl, 2-methylpentenyl, and 3-methylpentenyl.

[0043] A nitrile-substituted C1-C6 alkyl group, such as that selected from formonitrile, acetonitrile, propionitrile, 2-propionitrile, isobutyronitrile, sec-butyronitrile, tert-butyronitrile, n-pentanonitrile, isovaleritrile, tert-pentanonitrile, neopentanonitrile, n-hexanonitrile, and isonitrile.

[0044] The C2-C6 ynyl group is selected, for example, from ethynyl, propynyl, 2-propynyl, n-butynyl, isobutynyl, sec-butynyl, tert-butynyl, cyclobutynyl, n-pentynyl, isopentenynyl, tert-pentynyl, neopentynyl, cyclopentynyl, 2,2-dimethylpropynyl, 1-ethylpropynyl, 1-methylbutynyl, 2-methylbutynyl, n-hexynyl, isohexynyl, 2-hexynyl, 3-hexynyl, 2-methylpentynyl, and 3-methylpentynyl.

[0045] C1-C6 haloalkyl means that the C1-C6 alkyl group contains a halogen substituent. The halogen substituent may replace one H in the alkyl group, or it may replace multiple H in the alkyl group, or it may replace all H in the alkyl group. The halogen may be selected from F, Cl, Br, and I.

[0046] In one example, the haloalkyl group is a fluoroalkyl group.

[0047] In one example, R1, R2, R3, R4 and R5 are each independently selected from H, F, C1-C3 alkyl, C1-C3 haloalkyl, and C2-C3 alkynyl.

[0048] In one embodiment, at least one of R1, R2, R3, R4 and R5 is selected from C2-C6 ynyl groups, that is, the number of C2-C6 ynyl groups selected from R1, R2, R3, R4 and R5 is at least 1 (e.g., 1, 2, 3, 4, 5).

[0049] In one example, R5 is H in equations (Ⅳ), (Ⅷ), (Ⅴ), and (Ⅸ).

[0050] In one example, the first additive has the structure shown in formula (Ⅳ), wherein at least one of R1, R2, R3 and R4 is selected from C2-C6 alkynyl groups.

[0051] According to one specific embodiment, R1, R2, R3, R4 and R5 are each independently selected from H, F, C1-C3 alkyl, C1-C3 haloalkyl, C2-C3 alkynyl, and at least one of R1, R2, R3, R4 and R5 is selected from C2-C3 alkynyl.

[0052] In one example, the first additive has the structure shown in formula (Ⅳ), wherein at least one of R1, R2, R3 and R4 is selected from C2-C3 alkynyl groups.

[0053] In one example, at least one of R1, R2, R3, R4 and R5 is selected from C2-C6 alkynyl, and at least one is selected from C1-C6 fluoroalkyl, that is, the structure of the first additive contains both alkynyl and fluoroalkyl.

[0054] The alkynyl group can further enhance the interaction between the first additive and lithium ions, while the fluoroalkyl group can balance the electron cloud distribution density within the first additive molecule, thereby regulating the strength of the interaction with lithium ions. When both alkynyl and fluoroalkyl groups are present in the structure of the first additive, the interaction between the first additive and lithium ions can be regulated through the mutual restraint of these two groups, thereby further regulating the high-temperature performance and initial impedance of the electrolyte.

[0055] According to one specific embodiment, the first additive is selected from one or more of the following structures:

[0056]

[0057]

[0058]

[0059] The first additive can be obtained commercially or prepared using conventional preparation processes.

[0060] According to one specific embodiment, the content of the first additive is 0.1-3 wt% (e.g., 0.1 wt%, 0.5 wt%, 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt%, 3 wt%) based on the total weight of the electrolyte.

[0061] When the content of the first additive in the electrolyte is less than 0.1 wt%, a complete and dense SEI film cannot be formed on the surface of the negative electrode, and the cycle performance and high-temperature performance of the battery cannot be effectively improved. When the content of the first additive in the electrolyte is greater than 3 wt%, the SEI film formed on the surface of the negative electrode will be relatively thick, the internal resistance of the battery will be large, the internal polarization will be strong during charging and discharging, and the high-rate discharge performance and cycle performance of the battery will be reduced.

[0062] In one example, the content of the first additive is 0.5-2 wt% based on the total weight of the electrolyte.

[0063] In one example, the electrolyte further includes a third additive, which is ethylene monofluorocarbonate (FEC).

[0064] According to one specific embodiment, the content of the monofluoroethylene carbonate is 0.1-2 wt% (e.g., 0.1 wt%, 0.5 wt%, 1.0 wt%, 1.5 wt%, 2 wt%) based on the total weight of the electrolyte.

[0065] In one example, the content of the monofluoroethylene carbonate is 0.5-1.5 wt% based on the total weight of the electrolyte.

[0066] In one example, the weight ratio of the monofluoroethylene carbonate to the first additive is (0.33-20):1 (e.g., 0.33:1, 0.5:1, 1:1, 3:1, 5:1, 7:1, 10:1, 12:1, 15:1, 18:1, 20:1). The first additive works synergistically with the FEC to appropriately reduce the initial impedance of the battery.

[0067] In one example, the weight ratio of the monofluoroethylene carbonate to the first additive is (0.5-1):1.

[0068] According to one specific embodiment, the electrolyte further includes a second additive, which is selected from one or more of sulfonate compounds, a first lithium salt, and a silicon-containing compound.

[0069] In one example, the sulfonate compound has the structure shown in formula (VI-1) or (VI-2).

[0070] and / or R 10 R 11 Each is independently selected from C2-C8 alkyl, C2-C8 alkenyl, and C2-C8 alkynyl groups.

[0071] In one example, the sulfonate compound is selected from one or more of vinyl sulfate (DTD), 1,3-propanesulfonate lactone (PS), 1,4-butanesulfonate lactone, 1,5-pentanesulfonate lactone, 1,6-hexanesulfonate lactone, butenyl sulfate, pentenyl sulfate, and propylene sulfate (TS).

[0072] In one example, the first lithium salt is a fluorinated lithium salt, wherein the H atoms in the first lithium salt are replaced by F atoms, the number of F atoms being greater than 2 (e.g., 2, 4, 6), and / or all the H atoms in the first lithium salt are replaced by F atoms. The first lithium salt is an additive to the electrolyte.

[0073] In one example, the first lithium salt compound is selected from one or more of lithium difluorophosphate (LiPO2F2), lithium hexafluorophosphate (LiPF6), lithium difluorooxalate borate (LiDFOB), lithium bis(trifluoromethanesulfonyl)imide, lithium difluorobis(oxalate)phosphate, lithium tetrafluoroborate, lithium bis(oxalate)borate, lithium hexafluoroantimonyate, lithium hexafluoroarsenate, lithium di(trifluoromethanesulfonyl)imide, lithium di(pentafluoroethylsulfonyl)imide, lithium tri(trifluoromethanesulfonyl)methyl, and lithium di(trifluoromethanesulfonyl)imide.

[0074] In one example, the silicon-containing compound has The structure shown is provided in which M1, M2, M3, M4, M5, M6, M7, M8, and M9 are each independently selected from H, C1-C5 alkyl groups, and phenyl groups.

[0075] In one instance, M1, M2, M3, M4, M5, M6, M7, M8, and M9 may be the same or different, and each may be independently selected from H, C1-C3 alkyl, or phenyl.

[0076] In one example, the silicon-containing compound is selected from one or more of tris(trimethylsilane) phosphate (TMSP), trimethylsilane phosphate (TMS), methyl diphenylsilane phosphate (MDPS), triethylsilane phosphate (TES), dimethyl isopropylsilane phosphate (DMIPS), tert-butyl dimethylsilane phosphate (TBS), tert-butyl diphenylsilane phosphate (TBDPS), tert-hexyl dimethylsilane phosphate (TDS), and triisopropylsilane phosphate (TIPS).

[0077] According to one specific embodiment, the content of the second additive is 0.1-2 wt% (e.g., 0.1 wt%, 0.5 wt%, 1.0 wt%, 1.5 wt%, 2 wt%) based on the total weight of the electrolyte.

[0078] In one example, the content of the second additive is 0.5-1.5 wt% based on the total weight of the electrolyte.

[0079] In one example, the electrolyte includes the first additive and the second additive.

[0080] In one example, the weight ratio of the second additive to the first additive is (0.33-20):1 (e.g., 0.33:1, 0.5:1, 1:1, 3:1, 5:1, 7:1, 10:1, 12:1, 15:1, 18:1, 20:1).

[0081] The first additive and the second additive work synergistically to further improve the stability of the electrolyte, increase the battery capacity retention rate, avoid gas generation problems, and improve the battery's high-temperature storage performance and cycle stability.

[0082] In one example, the weight ratio of the second additive to the first additive is (0.5-1.5):1.

[0083] In one example, the electrolyte includes a first additive and a second additive containing at least the sulfonate compound.

[0084] According to one specific embodiment, the weight ratio of the sulfonate compound to the first additive is (0.33-20):1 (e.g., 0.33:1, 0.5:1, 1:1, 3:1, 5:1, 7:1, 10:1, 12:1, 15:1, 18:1, 20:1).

[0085] In one example, the weight ratio of the sulfonate compound to the first additive is (0.5-1.5):1.

[0086] According to one specific embodiment, the electrolyte further includes a second lithium salt and an organic solvent. The second lithium salt serves as the electrolyte in the electrolyte, primarily providing conductive ions.

[0087] In one example, the second lithium salt is selected from lithium difluorophosphate (LiPO2F2) and lithium hexafluorophosphate.

[0088] One or more of the following: (LiPF6), lithium difluorooxalate borate (LiDFOB), lithium bis(trifluoromethylsulfonyl)imide, lithium difluorobis(oxalate phosphate), lithium tetrafluoroborate, lithium bis(oxalate borate), lithium hexafluoroantimonyate, lithium hexafluoroarsenate, lithium di(trifluoromethylsulfonyl)imide, lithium di(pentafluoroethylsulfonyl)imide, lithium tri(trifluoromethylsulfonyl)methyl, and lithium di(trifluoromethylsulfonyl)imide.

[0089] In one example, the lithium salt content is 10-20 wt% based on the total weight of the electrolyte.

[0090] In one example, the organic solvent is selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (EMC), propyl acetate, n-butyl acetate, isobutyl acetate, n-pentyl acetate, isopentyl acetate, propyl propionate (PP), ethyl propionate (EP), methyl butyrate, and ethyl butyrate.

[0091] In one example, the content of the organic solvent is 77-89 wt% based on the total weight of the electrolyte.

[0092] The second invention provides a battery in which the electrolyte is the electrolyte described in the first aspect of the invention.

[0093] The batteries mentioned include lithium-ion batteries, sodium-ion batteries, and magnesium-ion batteries.

[0094] The materials and preparation methods for the battery, excluding the electrolyte, can be carried out in accordance with the practices in this field, and all of them can achieve the effects of low initial impedance, good high-temperature cycling performance, and more stable long-term cycling performance.

[0095] The battery can be a lithium-ion battery, such as a lithium cobalt oxide battery, a ternary nickel-cobalt-manganese battery, a ternary nickel-cobalt-aluminum battery, a lithium iron phosphate battery, a lithium manganese iron phosphate battery, a lithium manganese oxide battery, or a lithium nickel oxide battery.

[0096] The positive electrode of the battery may include one or more of transition metal oxides, lithium iron phosphate, and lithium-rich manganese-based materials, such as lithium cobalt oxide.

[0097] The negative electrode of the battery may include silicon-based materials and / or carbon-based materials, such as artificial graphite, natural graphite, mesophase carbon microspheres, hard carbon, soft carbon, nano-silicon, silicon-oxygen materials, and silicon-carbon materials.

[0098] Because the battery of the present invention contains the electrolyte described herein, the battery has a lower impedance growth rate, a higher capacity retention rate, improved high-temperature storage performance, and enhanced long-term cycle stability.

[0099] The present invention will be described in detail below through embodiments. The embodiments described herein are only a part of the embodiments of the present invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.

[0100] The following examples illustrate the electrolyte of the present invention.

[0101] Example 1

[0102] (1) Preparation of ingredients

[0103] First additive: 1 part by weight of having the structure shown in (Ⅳ-7);

[0104] Second additive: Sulfonate compounds: DTD1 parts by weight;

[0105] Organic solvents: EC: 24 parts by weight, DEC: 16 parts by weight, EMC: 40 parts by weight;

[0106] Lithium salt: LiPF6: 18 parts by weight.

[0107] (2) Electrolyte preparation

[0108] In an argon-filled glove box (moisture content <10ppm, oxygen content <10ppm), organic solvents are uniformly mixed, and lithium salt, first additive, and second additive are slowly added to the mixed solution to obtain the electrolyte for lithium-ion batteries.

[0109] Example 2 group

[0110] This set of examples is used to illustrate the effects of changing the weight ratio of the second additive to the first additive.

[0111] This set of embodiments is based on Embodiment 1, except that the weight ratio of the second additive to the first additive is changed, as detailed in Table 1.

[0112] Example 3 Group

[0113] This set of examples is used to illustrate the effects of changing the first additive.

[0114] This set of embodiments is based on Embodiment 1, except that the selection of the first additive is changed, as detailed in Table 1.

[0115] Example 4a

[0116] This embodiment is carried out with reference to Example 1, except that the second additive is changed to LiPO2F2, as detailed in Table 1;

[0117] Example 4b

[0118] This embodiment is carried out with reference to Example 1, except that the second additive is changed to TMSP, as detailed in Table 1;

[0119] Example 4c

[0120] This embodiment is carried out with reference to Example 3c, except that the second additive is changed to LiPO2F2, as detailed in Table 1;

[0121] Example 4d

[0122] This embodiment is carried out with reference to Example 3c, except that the second additive is changed to TMSP, as detailed in Table 1;

[0123] Example 4e

[0124] This embodiment is carried out with reference to Example 3f, except that the second additive is changed to LiPO2F2, as detailed in Table 1;

[0125] Example 4f

[0126] This embodiment is based on Example 3f, except that the second additive is changed to TMSP, as detailed in Table 1.

[0127] Example 5 group

[0128] This set of examples is used to illustrate the effects when the second additive is replaced with FEC.

[0129] Example 5a

[0130] This embodiment is carried out with reference to Embodiment 1, except that the second additive is replaced with FEC, as detailed in Table 1;

[0131] Example 5b

[0132] This embodiment is carried out with reference to Example 3a, except that the second additive is replaced with FEC, as detailed in Table 1;

[0133] Example 5c

[0134] This embodiment is carried out with reference to Embodiment 3c, except that the second additive is replaced with FEC, as detailed in Table 1;

[0135] Example 5d

[0136] This embodiment is carried out with reference to Example 3e, except that the second additive is replaced with FEC, as detailed in Table 1;

[0137] Example 5e

[0138] This embodiment is carried out with reference to Example 3f, except that the second additive is replaced with FEC, as detailed in Table 1;

[0139] Example 5f

[0140] This embodiment is carried out in accordance with Example 3g, except that the second additive is replaced with FEC, as detailed in Table 1;

[0141] Example 5g

[0142] This embodiment is carried out with reference to Example 3h, except that the second additive is replaced with FEC, as detailed in Table 1.

[0143] Example 6 group

[0144] This set of examples is used to illustrate the effects of not adding a second additive.

[0145] Example 6a

[0146] This embodiment is carried out with reference to Embodiment 1, except that no second additive is added and the weight parts of the organic solvent are adjusted so that the electrolyte is still 100 parts by weight.

[0147] Example 6b

[0148] This embodiment is carried out with reference to Embodiment 3a, except that no second additive is added and the weight parts of the organic solvent are adjusted so that the electrolyte is still 100 parts by weight.

[0149] Example 6c

[0150] This embodiment is carried out with reference to Embodiment 3b, except that no second additive is added and the weight parts of the organic solvent are adjusted so that the electrolyte is still 100 parts by weight.

[0151] Example 6d

[0152] This embodiment is carried out with reference to embodiment 3c, except that no second additive is added and the weight parts of the organic solvent are adjusted so that the electrolyte is still 100 parts by weight.

[0153] Example 6e

[0154] This embodiment is carried out with reference to embodiment 3d, except that no second additive is added and the weight parts of the organic solvent are adjusted so that the electrolyte is still 100 parts by weight.

[0155] Example 6f

[0156] This embodiment is carried out with reference to Embodiment 3e, except that no second additive is added and the weight parts of the organic solvent are adjusted so that the electrolyte is still 100 parts by weight.

[0157] Example 6g

[0158] This embodiment is carried out with reference to Embodiment 3f, except that no second additive is added and the weight parts of the organic solvent are adjusted so that the electrolyte is still 100 parts by weight.

[0159] Example 6h

[0160] This embodiment is carried out in accordance with the example 3g, except that no second additive is added and the weight of the organic solvent is adjusted so that the electrolyte is still 100 parts by weight.

[0161] Example 6i

[0162] This embodiment is carried out with reference to Example 3h, except that no second additive is added and the weight parts of the organic solvent are adjusted so that the electrolyte is still 100 parts by weight.

[0163] Example 7 group

[0164] This set of examples is used to illustrate the effects of changing the content of the first additive.

[0165] This set of embodiments is based on Embodiment 5, except that the weight parts of the first additive are changed, as detailed in Table 1.

[0166] Table 1

[0167]

[0168]

[0169]

[0170]

[0171] Comparative Example 1

[0172] The procedure was carried out in accordance with Example 1, except that no first additive and second additive were added to the electrolyte.

[0173] Comparative Example 2

[0174] This comparative group is used to illustrate the effect of not adding the first additive.

[0175] Comparative Example 2a

[0176] The procedure was carried out in accordance with Example 1, except that no first additive was added to the electrolyte;

[0177] Comparative Example 2b

[0178] The procedure was carried out in accordance with Example 4a, except that the first additive was not added to the electrolyte;

[0179] Comparative Example 2c

[0180] The procedure was carried out in accordance with Example 4b, except that the first additive was not added to the electrolyte.

[0181] Comparative Example 3 Groups

[0182] This comparative example group is used to illustrate the effects of replacing the first additive with other additives.

[0183] Comparative Example 3a

[0184] The procedure was carried out in accordance with Example 6a, except that the first additive was replaced with PS;

[0185] Comparative Example 3b

[0186] The procedure was carried out in accordance with Example 6a, except that the first additive was replaced with PST;

[0187] Comparative Example 3c

[0188] The procedure was carried out in accordance with Example 6a, except that the first additive was replaced with VEC.

[0189] Preparation Example

[0190] Batteries were prepared using the electrolytes obtained in the examples and comparative examples, respectively, in the following manner:

[0191] (1) Preparation of positive electrode

[0192] The cathode material ratio is LiNi 0.8 Co 0.15 Mn 0.05 O2, acetylene black, and polyvinylidene fluoride (PVDF) in a mass ratio of 94:3:3; PVDF is added to N-methylpyrrolidone (NMP) and stirred at high speed until completely dissolved to form a homogeneous solution; acetylene black is added to the solution and stirred evenly; then ternary materials are added and stirred to form a homogeneous positive electrode slurry; the positive electrode slurry is coated onto an aluminum foil current collector, and the electrode is baked, compacted, cut, and the tabs are welded.

[0193] (2) Preparation of negative electrode

[0194] The negative electrode material is formulated with artificial graphite, acetylene black, styrene-butadiene rubber (SBR), and sodium carboxymethyl cellulose (CMC) in a mass ratio of 94:1.5:2.5:2. CMC is added to water and stirred at high speed until completely dissolved. Then, acetylene black is added and stirring continues until homogeneous. Artificial graphite powder is then added and stirred until evenly dispersed. Finally, SBR is added and dispersed into a uniform negative electrode slurry. The negative electrode slurry is coated onto a copper foil current collector, and the electrode is baked and compacted. The electrode is then cut and the tabs are welded.

[0195] (3) Electrolyte preparation

[0196] The electrolytes obtained in the above-described embodiments and comparative examples were used respectively.

[0197] (4) Preparation of lithium-ion batteries

[0198] The positive electrode sheet, separator and negative electrode sheet from step (1) are wound together into a core, sealed with aluminum-plastic film and then baked to meet the requirements for electrode moisture content. After baking, the cell is injected with electrolyte and then subjected to standing, formation, capacity testing and aging processes to obtain a soft-pack lithium-ion power battery with a capacity of 1000mAh.

[0199] Test case

[0200] The batteries obtained in the examples and comparative examples were subjected to the following tests:

[0201] (1) Capacity retention rate after 500 cycles at 45℃

[0202] The battery was charged and discharged for 500 cycles at 45°C at a rate of 1C within the charge and discharge cutoff voltage range. The discharge capacity of the first cycle was measured as x1 mAh, and the discharge capacity of the 500th cycle was measured as y1 mAh. The capacity of the 500th cycle was divided by the capacity of the first cycle to obtain the cycle capacity retention rate R1 = y1 / x1.

[0203] The capacity retention test results of the battery obtained with the electrolyte in Example 1 after 500 cycles at 45°C are as follows: Figure 1 As shown.

[0204] (2) Capacity retention rate at 60℃ for 30 days

[0205] The battery was charged and discharged at 25℃ at a rate of 1C within the charge and discharge cutoff voltage range. The result measured by the discharge capacity meter was x2 mAh. Then, the battery was left at 60℃ in an open circuit state for 30 days. The battery was then discharged at a constant current of 1C. The result measured by the discharge capacity meter was y1 mAh. The capacity retention rate after 30 days of high-temperature storage at 60℃ was obtained as R2 = y2 / x2.

[0206] (3) Measurement of the initial DCR of the battery

[0207] The battery was intermittently discharged at a constant current of 1A for 20 minutes, followed by a 5-minute rest period (the stabilization time is determined by the system, and this process can be continuously cycled until the termination voltage is reached). The battery voltage before the discharge was terminated and the battery voltage after the voltage stabilized were recorded. Then, the DC impedance was calculated using the following formula (where: ΔU is the voltage difference, DCR is the DC resistance, and I is the discharge current):

[0208] DCR=ΔU / I.

[0209] The percentage of the initial DCR of the battery relative to Example 1 = (initial DCR of the battery / initial DCR of the battery obtained with the electrolyte of Example 1) * 100%. The results are recorded in Table 2.

[0210] Table 2

[0211]

[0212]

[0213]

[0214] As can be seen from Table 2, compared with Comparative Example 1, the battery capacity retention rate of the electrolyte in Example 6 is significantly improved and the initial DCR is significantly reduced. This indicates that the introduction of the first additive of the present invention improves the stability of the electrolyte and reduces the impedance of the electrolyte.

[0215] As can be seen from Examples 5 and 6, the initial DCR of the battery prepared with the electrolyte in Example 5 was significantly reduced, indicating that the combination of the first additive of the present invention and FEC can further reduce the impedance of the electrolyte.

[0216] As can be seen from Examples 1, 3, 4, and 6, the battery capacity retention rate of the electrolytes prepared in Examples 1, 3, and 4 is significantly improved, indicating that the combination of the first additive and the second additive of the present invention can further improve the stability of the electrolyte.

[0217] As can be seen from the comparative examples and embodiments, the battery capacity retention rate of the electrolyte prepared in the embodiments is significantly improved and the initial DCR is reduced. This indicates that the introduction of the first and second additives and FEC of the present invention improves the stability of the electrolyte, reduces the impedance of the electrolyte, thereby improving the battery capacity retention rate and reducing the battery initial impedance.

[0218] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. An electrolyte, characterized in that, The electrolyte includes a first additive, which is a bridged cyclic olefin compound or its derivative, and the first additive has the structure shown in formula (I). (I), where n is 0, 1, or 2; When n is 0, the first additive has the structure shown in formula (II) and / or formula (III). (Ⅱ)、 (Ⅲ); And / or; if n is 1, the first additive has the structure shown in formula (IV) and / or formula (VIII), (Ⅳ)、 (Ⅷ); And / or; n is 2, the first additive has the structure shown in formula (V) and / or formula (IX), (Ⅴ)、 (Ⅸ); In formulas (III), (II), (IV), (VIII), (VIII), and (IX), R1, R2, R3, R4, and R5 are each independently selected from H, F, Cl, Br, I, C1-C6 alkyl, C1-C6 haloalkyl, nitrile-substituted C1-C6 alkyl, C2-C6 alkenyl, and C2-C6 alkynyl, and at least one of R1, R2, R3, R4, and R5 is selected from C2-C6 alkynyl, and at least one of them is selected from C1-C6 fluoroalkyl; Based on the total weight of the electrolyte, the content of the first additive is 0.1-3 wt%.

2. The electrolyte according to claim 1, wherein, R1, R2, R3, R4 and R5 are each independently selected from H, F, C1-C3 alkyl, C1-C3 haloalkyl, C2-C3 alkynyl, and at least one of R1, R2, R3, R4 and R5 is selected from C2-C3 alkynyl, and at least one of them is selected from C1-C6 fluoroalkyl.

3. The electrolyte according to claim 1, wherein, The first additive is selected from one or more of the following structures: (Ⅱ-6)、 (Ⅱ-7)、 (Ⅲ-6)、 (Ⅲ-7)、 (Ⅳ-6)、 (Ⅳ-7)、 (Ⅷ-6)、 (Ⅷ-7)、 (Ⅴ-6)、 (Ⅴ-7)、 (Ⅸ-6)、 (Ⅸ-7)。 4. The electrolyte according to claim 1, wherein, The electrolyte further includes a third additive, which is ethylene monofluorocarbonate, and the content of ethylene monofluorocarbonate is 0.1-2 wt%; and / or, The weight ratio of the monofluoroethylene carbonate to the first additive is (0.33-20):

1.

5. The electrolyte according to claim 1, wherein, The electrolyte further includes a second additive, which is selected from one or more of sulfonate compounds, a first lithium salt, and silicon-containing compounds; And / or, based on the total weight of the electrolyte, the content of the second additive is 0.1-2 wt%.

6. The electrolyte according to claim 5, wherein, The sulfonate compounds have the formula (VI-1) and / or The structure shown in (VI-2) has R 10 R 11 Each is independently selected from C2-C8 alkyl, C2-C8 alkenyl, and C2-C8 alkynyl groups; the first lithium salt is a fluorinated lithium salt, wherein the H atoms in the first lithium salt are replaced by F atoms, and the number of F atoms is greater than 2; And / or; the silicon-containing compound has The structure shown in (VII) is wherein M1, M2, M3, M4, M5, M6, M7, M8, and M9 are each independently selected from H, C1-C5 alkyl, and phenyl.

7. The electrolyte according to claim 5, wherein, The sulfonate compound is selected from one or more of vinyl sulfate, 1,3-propanesulfonate lactone, 1,4-butanesulfonate lactone, 1,5-pentanesulfonate lactone, 1,6-hexanesulfonate lactone, butenyl sulfate, pentenyl sulfate, and propylene sulfate; and / or, The first lithium salt is selected from one or more of lithium difluorophosphate, lithium hexafluorophosphate, lithium difluorooxalate borate, lithium difluorobis(oxalate) phosphate, lithium tetrafluoroborate, lithium bis(oxalate) borate, lithium hexafluoroantimonyate, lithium hexafluoroarsenate, lithium di(pentafluoroethylsulfonyl)imide, lithium tri(trifluoromethylsulfonyl)methyl, and lithium di(trifluoromethylsulfonyl)imide; and / or, The silicon-containing compound is selected from one or more of tris(trimethylsilane) phosphate, trimethylsilane phosphate, methyl diphenylsilane phosphate, triethylsilane phosphate, dimethyl isopropylsilane phosphate, tert-butyl dimethylsilane phosphate, tert-butyl diphenylsilane phosphate, tert-hexyl dimethylsilane phosphate, and triisopropylsilane phosphate.

8. The electrolyte according to any one of claims 5-7, wherein, The weight ratio of the second additive to the first additive is (0.33-20):

1.

9. The electrolyte according to claim 8, wherein, The weight ratio of the sulfonate compound to the first additive is (0.33-20):

1.

10. A battery, characterized in that, The battery includes the electrolyte as described in any one of claims 1-9.

Citation Information

Patent Citations

  • Lithium ion battery electrolyte and lithium ion battery comprising same

    CN108598574A

  • Nonaqueous electrolyte secondary battery

    JP2003109659A